Understanding why patients with substance use disorders leave the hospital against medical advice: A qualitative study. Issue 4 (1st October 2020) - Simon, Rachel; Snow, Rachel; Wakeman, Sarah
Abstract: Background: Hospital discharges against medical advice (AMA) is associated with negative health outcomes and re-admissions. Patients with substance use disorders (SUD) are up to three times more likely to be discharged AMA as compared to those without SUD. Studies suggest that undertreated withdrawal and a perception of stigma may increase the risk, however, to date, there are no published qualitative studies exploring the specific reasons why patients with SUD leave prematurely. Methods: Semi-structured interviews with patients ( n = 15) with SUD with documented AMA discharges from our hospital between 9/2017 and 9/2018. Maximum variation sampling was employed to display diversity across gender, race, age, and type of substance use disorder (alcohol vs opioids). Patients were interviewed until no new concepts emerged from additional interviews. Two coders separately coded all transcripts and reconciled code assignments. Results: Four core issues were identified as patients' reasons for leaving the hospital prematurely: undertreated withdrawal and ongoing craving to use drugs, uncontrolled acute and chronic pain, stigma and discrimination by hospital staff about their SUD, and hospital restrictions, including not being allowed to intermittently leave the hospital floor. For patients with histories of criminal involvement, being hospitalized reminded them of being incarcerated. Conclusion: These findings shed light on the reasons patients with SUD are discharged from the hospital AMA, an event that is associated with increased thirty-day mortality and hospital re-admission. AMA discharges represent missed opportunities for the health care system to engage with patients struggling with a SUD. Our findings support the need for inpatient addiction treatment, particularly for management of withdrawal and co-occurring pain, and the need to address health care provider associated stigma surrounding addiction.